Macroeconomic stabilisation and monetary policy effectiveness in a low-interest-rate environment - Günter Coenen; Carlos Montes-Galdón; Sebastian Schmidt (European Central Bank (ECB), 2021)
The secular decline in the equilibrium real interest rate observed over the past decades has materially limited the room for policy-rate reductions in recessions, and has led to a marked increase in the incidence of episodes where policy rates are likely to be at, or near, the effective lower bound on nominal interest rates. Using the ECB's New Area-Wide Model, we show that, if unaddressed, the effective lower bound can cause substantial costs in terms of worsened macroeconomic performance, as re ected in negative biases in in ation and economic activity, as well as heightened macroeconomic volatility. These costs can be mitigated by the use of nonstandard instruments, notably the joint use of interest-rate forward guidance and large-scale asset purchases. When considering alternatives to in ation targeting, we find that make-up strategies such as price-level targeting and average-in ation targeting can, if they are well-understood by the private sector, largely undo the negative biases and heightened volatility induced by the effective lower bound.
Keywords: E31; E32; E37; E52; E58; 330; Effective lower bound; monetary policy; asset purchases; forward guidance; make-up strategies